Walls of Vienna - Batty, Robert, 1789-1848 (artist):::Creator::::::::::::; Heath, Charles, 1785-1848 (engraver):::Contributor:::::::::::: (London; Rodwell & Martin; United Kingdom)
Color engraving of Vienna viewed from the Danube River